Dos calles y una chica - Ma, Eve A.; Malena, Antonio de la; Palomino Productions ([Berkeley, California] : Palomino Productions, 2014)
Two Streets and Adela allows us to get to know a person whose life, while not dramatic, is full of color and art. In addition, we observe and learn the character of a charming city in southern Spain, a city (Jerez de la Frontera) known as the 'cradle of flamenco.' It is its connection with flamenco that allows our heroine to successfully make a living as a flamenco dance costume designer and seamstress--
Originally released as a motion picture in 2014
Adela Olmos, Saira Moreno Jime nez
Narrator, Antonio de la Malena
In Spanish; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 25, 2018)
Keywords: Women tailors -- Spain -- Jerez de la Frontera -- Drama; Jerez de la Frontera (Spain) -- Social life and customs -- Drama; Jerez de la Frontera (Spain); Short films; Nonfiction films; Flamenco music; Internet videos; Streaming video